12/15-Lipoxygenase Inhibition or Knockout Reduces Warfarin-Associated Hemorrhagic Transformation After Experimental Stroke. Issue 2 (February 2017) - Liu, Yu; Zheng, Yi; Karatas, Hulya; Wang, Xiaoying; Foerch, Christian; Lo, Eng H.; van Leyen, Klaus
Abstract : Background and Purpose—: For stroke prevention, patients with atrial fibrillation typically receive oral anticoagulation. The commonly used anticoagulant warfarin increases the risk of hemorrhagic transformation (HT) when a stroke occurs; tissue-type plasminogen activator treatment is therefore restricted in these patients. This study was designed to test the hypothesis that 12/15-lipoxygenase (12/15-LOX) inhibition would reduce HT in warfarin-treated mice subjected to experimental stroke. Methods—: Warfarin was dosed orally in drinking water, and international normalized ratio values were determined using a Coaguchek device. C57BL6J mice or 12/15-LOX knockout mice were subjected to transient middle cerebral artery occlusion with 3 hours severe ischemia (model A) or 2 hours ischemia and tissue-type plasminogen activator infusion (model B), with or without the 12/15-LOX inhibitor ML351. Hemoglobin was determined in brain homogenates, and hemorrhage areas on the brain surface and in brain sections were measured. 12/15-LOX expression was detected by immunohistochemistry. Results—: Warfarin treatment resulted in reproducible increased international normalized ratio values and significant HT in both models. 12/15-LOX knockout mice suffered less HT after severe ischemia, and ML351 reduced HT in wild-type mice. When normalized to infarct size, ML351 still independently reduced hemorrhage. HT after tissue-type plasminogen activator was similarly reduced by ML351. Conclusions—: In addition to its benefits in infarct size reduction, 12/15-LOX inhibition also may independently reduce HT in warfarin-treated mice. ML351 should be further evaluated as stroke treatment in anticoagulated patients suffering a stroke, either alone or in conjunction with tissue-type plasminogen activator. Abstract : Supplemental Digital Content is available in the text.